Enterovirus-D68 in the Cerebrospinal Fluid of Two Children with Aseptic Meningitis. Issue 5 (May 2016) - Esposito, Susanna; Lunghi, Giovanna; Zampiero, Alberto; Tagliabue, Claudia; Orlandi, Anna; Torresani, Erminio; Niesters, Hubert; Principi, Nicola
Abstract : This case report describes two previously healthy children with aseptic meningitis whose cerebrospinal fluid was positive for enterovirus-D68, which indicates direct involvement of this infectious agent in the development of this neurologic disease.